Assessment of Damaged Infrastructure Due To Flash Floods and Landslides in Tanah Datar And Agam Regencies, West Sumatra Province: Asesmen Infrastruktur Yang Rusak Akibat Bencana Banjir Bandang dan Tanah Longsor di Kabupaten Tanah Datar dan Agam, Provinsi Sumatera Barat - Fauzan, Fauzan; Bambang Istijono; Febrin Anas Ismail; Abdul Hakam; Yenny Narny; Geby Aryo Agista; Aditya Abdi Pratama; Cindy Murdiaman Guci (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
On Saturday, May 11, 2024, a natural disaster involving cold lahar floods and landslides occurred in Tanah Datar and Agam Regencies, West Sumatra Province. This disaster was triggered by high-intensity rainfall upstream of Mount Marapi, which caused rain-induced lahar flows. Moderate to heavy rainfall eroded and carried volcanic sediment deposits, forming lahar flows. The disaster caused significant damage, including destruction of infrastructure such as roads and bridges, public buildings like mosques and offices, residential houses, and loss of lives. In response to the disaster, Andalas University, through its Disaster Response Center Team from the Research and Community Service Institute (LPPM), conducted a site survey of the affected areas on Monday, May 13, 2024. This community service activity was carried out to assess the damaged infrastructure caused by the flash floods, providing solutions and recommendations for repair and reinforcement, and ensuring the infrastructure's usability post-disaster. This community service (PkM-P) activity was carried out using a comprehensive methodological approach employing field survey techniques. The survey was conducted to gain a clear understanding of the physical condition of the cliffs and their surrounding environment along the Padang-Bukittinggi national road at the coordinates 0°29'36"S 100°20'20"E, which are in a critical state following the Anai River flash flood. The activities included preparation and planning, field surveys, data collection and analysis, as well as reporting and recommendations. The assessment results indicated that the previously implemented methods failed to withstand the high flood pressure. Recommendations for repair and reinforcement include the construction of levees and stream diversions in the Anai River, road drainage systems, planting stronger vegetation, road realignment, and routine monitoring.